Not Just Survive, But Thrive: Examining Livelihood Capital, Poverty Reduction, and Sustainable Development in Ethnic Tourism Destinations - Huang, Yanling; Feng, Min; (Robert) Li, Xiang (Cornell hospitality quarterly, 2025)
Understanding the roles of tourism development in poverty reduction and livelihood capital through a microlens is essential to rural ethnic areas’ sustainable development. However, few assessment methods are available to unravel the complex relationships between these three facets, and gaps remain in measuring residents’ livelihood. Based on the sustainable livelihood approach, this paper first selected core components of the sustainable livelihood framework to construct an evaluation index system and then provided specific indicators and evaluative criteria. Taking villages in China’s Longji Rice Terraces as a sample case, this study employed objective approaches (e.g., the entropy weight method and gray relational analysis) to assess residents’ livelihood capital. The aim was to showcase the sustainability of this area’s livelihood through a microlens. Findings offer several important contributions. First, this study presents a reliable measurement development method and a set of evaluation criteria for sustainable livelihood in tourism contexts, including five forms of capital and 21 indicators. Second, local inhabitants were found to benefit from tourism development; their livelihood options were diversified, especially in terms of growing financial capital. Yet these benefits were not evenly distributed, with notable differences observed across communities. Third, farmers’ livelihood capability did not improve uniformly over time. These findings offer valuable insights for tourism and hospitality stakeholders and can help steer rural regions toward a path of prosperity and growth. Strategies for inspiring entrepreneurship should especially be considered. In closing, theoretical implications are discussed, and suggestions for future work are provided.